Question

(5) \[ \begin{array}{l} 3 x^{2}-3(x-1)=4(2 x+1)+3 \\ x^{2}=x \end{array} \]

Ask by Thornton Tucker. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

There is no solution to the system of equations. **Answer:** No solution exists for the given system.

Solution

Let's solve the given system of equations step by step: \[ \begin{cases} 3x^{2} - 3(x - 1) = 4(2x + 1) + 3 \\ x^{2} = x \end{cases} \] ### Step 1: Solve the Second Equation The second equation is: \[ x^{2} = x \] Subtract \( x \) from both sides to set the equation to zero: \[ x^{2} - x = 0 \] Factor out \( x \): \[ x(x - 1) = 0 \] So, the solutions are: \[ x = 0 \quad \text{or} \quad x = 1 \] ### Step 2: Substitute the Solutions into the First Equation Now, let's check if these solutions satisfy the first equation. **First Solution: \( x = 0 \)** Substitute \( x = 0 \) into the first equation: \[ 3(0)^2 - 3(0 - 1) = 4(2(0) + 1) + 3 \] \[ 0 - (-3) = 4(0 + 1) + 3 \] \[ 3 = 4 \cdot 1 + 3 \] \[ 3 = 7 \] This is **not true**. **Second Solution: \( x = 1 \)** Substitute \( x = 1 \) into the first equation: \[ 3(1)^2 - 3(1 - 1) = 4(2(1) + 1) + 3 \] \[ 3 - 0 = 4(2 + 1) + 3 \] \[ 3 = 12 + 3 \] \[ 3 = 15 \] This is also **not true**. ### Conclusion Neither of the solutions from the second equation (\( x = 0 \) or \( x = 1 \)) satisfies the first equation. Therefore, **the system has no solution**. **Answer:** There is no real solution to the system; no value of x satisfies both equations simultaneously.

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Beyond the Answer

To solve the equation, let's first simplify the first equation step by step: Starting with: \[ 3 x^{2}-3(x-1)=4(2 x+1)+3 \] Distributing \( -3 \) and \( 4 \): \[ 3 x^{2} - 3x + 3 = 8x + 4 + 3 \] \[ 3 x^{2} - 3x + 3 = 8x + 7 \] Now, rearranging everything to one side gives us: \[ 3 x^{2} - 3x - 8x + 3 - 7 = 0 \] \[ 3 x^{2} - 11x - 4 = 0 \] Next, we can apply the quadratic formula \( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \), where \( a = 3 \), \( b = -11 \), and \( c = -4 \): \[ x = \frac{11 \pm \sqrt{(-11)^2 - 4 \cdot 3 \cdot (-4)}}{2 \cdot 3} \] \[ x = \frac{11 \pm \sqrt{121 + 48}}{6} \] \[ x = \frac{11 \pm \sqrt{169}}{6} \] \[ x = \frac{11 \pm 13}{6} \] Calculating the two potential solutions: 1. \( x = \frac{24}{6} = 4 \) 2. \( x = \frac{-2}{6} = -\frac{1}{3} \) So, the solutions are: \[ x = 4 \quad \text{and} \quad x = -\frac{1}{3} \] Now turning to our second equation: \[ x^{2}=x \] This can be rewritten as: \[ x^{2} - x = 0 \] Factoring gives: \[ x(x - 1) = 0 \] From this factored form, we see that \( x = 0 \) or \( x = 1 \). In summary, the solutions to the first equation are \( x = 4 \) and \( x = -\frac{1}{3} \), while the solutions to the second equation are \( x = 0 \) and \( x = 1 \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy